التغيرات الفصلية لمجتمعات الأكاروسات العنكبوتية و الأكاروس المفترس Typhlodromus athiasae (Acari: Phytoseiidae) في بساتين التفاح في محافظة حمص - صقر, ابراهيم; مفلح, ماجدة; بشير, عبد النبي; ضحية, حمزة (Latakia University Journal -Biological Sciences Series, 2016)
هدف البحث إلى دراسة التغيرات الفصلية لمجتمعات الأكاروسات العنكبوتية والأكاروس المفترس Typhlodromus athiasae Porath and Swirski على صنفي التفاح غولدن و ريد ديليشز في بساتين التفاح في منطقتي المخرم و القصير خلال الفترة الواقعة بين بداية شهر أيار لعام 2013و نهاية شهر تشرين الأول 2014. بيّنت النتائج أن أعلى كثافة تصل إليها الأكاروسات العنكبوتية في مرحلتين أساسيتين في أوائل و منتصف الصيف, أما بالنسبة للمفترس Typhlodromus athiasae فبدأ نشاطه مع بداية نشاط الفريسة في شهر أيار وكانت ذروة أعداده في تموز. كانت الكثافة المتوسطة للأكاروس المفترس و الأكاروسات العنكبوتية أعلى بشكل معنوي على الصنف ريد ديليشز بالمقارنة مع الصنف غولدن و كان تواجدها في منطقة القصير أعلى بالمقارنة في منطقة المخرم مع وجود فروق معنوية. كما لوحظ أيضاً تواجد المفترس على بعض النباتات الطبيعية المتواجدة داخل أو حول هذه البساتين.The aim of the research was to study seasonal changes communities of spider mites and predatory mite Typhlodromus athiasae Porath and Swirski on two apple cultivars (Golden and red Delicious) from orchards located in two regions: Al-Mokharam and Al-Qusayr during the beginning May 2013 and the end of October 2014. The results showed that the highest density of the spider mites was in two essential period in early and mid summer, while T.athiasae started its active with started pery active, that started appear in the may, and the top of its number was in July, The mean density of the mite predator and spider mites was higher on the red Delicious apple cultivar compared to Golden Delicious with significant differences, and its presence was higher in the Al-Qusayr region compared to the Al-Mokharam region with significant differences, also remarked this predator on some surrounding vegetation in these orchards.